Tumor odontogênico queratocístico: considerações clínico-cirúrgico - Carvalho, Abrahão Cavalcante Gomes de Souza; Pereira, Cassiano Costa Silva [UNESP]; Gaetti-Jardim, Ellen Cristina [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Magro Filho, Osvaldo [UNESP] (My University, 2012)
Introduction: The tumor odontogenic keratocyst (toq) is a benign disorder, which is controversial in its diagnosis and treatment. It is characterized by a true neoplasms arising from remnants the dental lamina. It occurs predominantly in the angle mandible, which may or may not be related to a tooth and whose importance is due to its aggressive behavior and high recurrence rate. The causes of the high recurrence rates. The thin capsule and friable tissue may favor the toq retention of epithelial debris and, moreover, the presence of satellite cells in the lesion site is responsible for the increased proliferative capacity of clinical entity. Objective: To present the peculiarities toq inherent in using a clinical case of toq in mandible. Case report: TOQ in the jaw in patient, 16 years old male presenting important lesion radiographically radiolucent related to the impacted tooth. Final comments: In consideration of the high rate of recurrence chosen treatment proved effective and was not any evidence of recurrence.

Introdução: O tumor odontogênico queratocístico (TOQ) é uma patologia benigna, que apresenta controvérsias em seu diagnóstico e tratamento. Caracteriza-se por uma neoplasia verdadeira originada a partir de remanescentes da lâmina dentária. Ocorre predominantemente no ângulo mandibular, podendo estar ou não relacionados a um elemento dentário e cuja importância deve-se ao seu comportamento agressivo e alta taxa de recorrência. As causas dos altos índices de recidiva. A cápsula delgada e friável de tecido conjuntivo dos TOQ pode favorecer a permanência de restos epiteliais e, além disso, a presença de células satélites no sítio da lesão é responsável pela elevada capacidade proliferativa dessa entidade clínica. Objetivo: Apresentar as peculiaridades inerentes ao TOQ por meio de um caso clínico de TOQ em mandíbula. Caso clínico: Exuberante TOQ em mandíbula, em paciente de 16 anos de idade do gênero masculino apresentando radiograficamente importante lesão radiolúcida relacionada a dente incluso. Comentários finais: Em consideração a grande taxa de recorrência o tratamento escolhido mostrou-se eficaz e não foi observado qualquer sinal de recidiva da lesão.
Keratocyst odontogenic tumor: clinical and surgical considerations
Keywords: Neoplasms; Recurrence; Therapeutics; Neoplasias; Recidiva; Terapêutica